Biosecurity and One Health Integration: An Extensive Analysis of Methods for Preventing Emerging Infectious Diseases - Fiaz, Muhammad Awais; Aqib, Muhammad; Zaman, Haider; Ali, Asim; Rauf, Umber; Sodager, Muhammad Abdul Hannan; Ahmad, Maqsood; Nasir, Kamran Ahmad; Mughal, Zain Ul Abideen; Abdullah, Obaid Muhammad; Sabir, Anum (Indus Journal of Bioscience Research, 2025)
This review analyzes the combination of biosecurity protocols with the One Health framework in mitigating emerging infectious diseases (EIDs), which pose an increasing global health risk. Emerging infectious diseases (EIDs), frequently zoonotic, present substantial threats to human, animal, and environmental Health, underscoring the necessity for cooperative initiatives between biosecurity and One Health paradigms. This review consolidates available evidence to assess the efficacy of these integrated techniques, highlighting significant trends, problems, and deficiencies in present practices. It emphasizes the alignment of biosecurity measures, including monitoring systems and risk management strategies, with the One Health framework to enhance early detection, prevention, and response to infectious diseases. Despite substantial advancements, notable deficiencies persist, especially in the uniformity of implementation techniques across various locations and sectors. The paper analyzes the constraints of existing methodologies, emphasizing the disunity of initiatives and difficulties in resource distribution, especially in low-income environments. Additionally, it examines the significance of international cooperation and frameworks, such as the Global Health Security Agenda (GHSA), in promoting collaboration among human, animal, and environmental health sectors. In summary, the review offers recommendations for future research, highlighting the necessity for longitudinal studies, enhanced policy frameworks, and the establishment of standardized protocols to strengthen the integration of biosecurity and One Health. These findings provide critical insights for policymakers, researchers, and practitioners, thereby enhancing global health initiatives to prevent and control new infectious diseases.